Pemberdayaan Ekonomi dan Pencegahaan Stunting melalui Pelatihan Pembuatan Produk Inovasi Stik Daun Kelor terhadap Ibu-Ibu PKK Desa Kedungbanjar: Pengabdian - Erdila Yuni Safitri; Achmad Farid Dedyansyah; Ilhmad Basri K; A’aliyah Khoirun Nisa’; M. Ary Dhuta Kirana; Sefininda Desfia Ardianah; Umi Atiyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
In general, the people of Kedungbanjar Village rely on the agricultural and entrepreneurial sectors. The fertile land of Kedungbanjar Village makes many plants grow well there, including Moringa plants. However, the people of Kedungbajar Village still have minimal skills to utilize Moringa plants (Moringa oleifera). Moringa plants that grow abundantly in Kedungbanjar Village can actually be used as one of the mainstay commodities that can be developed further to support the community's economy and to prevent stunting. The method used is to provide training to PKK mothers in Kedungbanjar Village, Sugio District, Lamongan Regency, which begins with conducting observations first regarding the potential in Kedungbanjar Village and analyzing community conditions, then continuing with analyzing the needs of the community, and preparing plans for what to do next. The second stage is to conduct socialization to residents about the benefits of Moringa leaves (Moringa oleifera). The third stage is to provide training in making Moringa leaf sticks to PKK mothers in Kedungbanjar Village. The fourth stage is evaluation and continued mentoring after the training ends until the PKK mothers can independently increase the selling value of the Moringa leaf sticks.